Rapid Growth Rate and Higher Yield Potential of Heterotic Eucalyptus Species Hybrids FRI-4 and FRI-5 - Venkatesh, C. S.; Sharma, V. K. (Indian Forester, 1977)
In pilot field trials established in 1972-73 at Dehra Dun heterotic F4 hybrids of the Eucalyptus species crosses FRI-4 (E. tereticornis Ã— E. camaldulensis) and FRI-5 E. camaldulensis Ã— E. tereticornis showed very rapid height and diameter growth increment and by age 4, dramatically excelled the parental controls by 271% and Mysore Gum (Mysore Hybrid) by 109% in mean standing volume. Since mass production de novo of F1 hybrid seed is difficult and will at any rate involve much time, therefore tested and pedigreed F2 seed has been released instead as breeder material for multilocation performance and yield trials of these promiting and potentially very high wood yielding hybrid tree varieties. Independently, progeny test results indicate that selective breeding within existing Mysore Gum. populations could give first generation genetic gains of as much as 46% in volume.